SOCIAL MEDIA MARKETING INTENSITY, BRAND AUTHENTICITY, AND ELECTRONIC WORD OF MOUTH AS PREDICTORS OF PURCHASE INTENTION OF PRODUCT BRANDS ON TIK TOK SHOP - Emilia Septiani; Farida Farida; Rr. Chusnu Syarifa Diah Kusuma; Ighomereho O. Salome; Javad Karimi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
In the rapidly evolving social commerce landscape, particularly through the TikTok platform and its TikTok Shop feature, understanding the determinants of consumer purchase intentions is becoming increasingly crucial. Still, it reveals conceptual gaps stemming from research approaches that are often partial. Previous studies generally examine social media marketing, brand authenticity, or electronic word of mouth (e-Wom) separately, and thus have not been able to explain the simultaneous interaction among these variables within a single integrative framework. This research aims to comprehensively analyze the influence of social media marketing intensity, brand authenticity, and e-WOM on purchase intention. Using a quantitative approach with structural equation modelling–partial least squares (SEM-PLS) analysis, data were collected from 110 respondents in Indonesia who had experience interacting with TikTok Shop. The research results show that social media marketing intensity has a significant positive effect on brand authenticity and e-Wom, which, in turn, strongly increases Purchase Intention, with brand authenticity acting as a key mediator. These findings make theoretical contributions by integrating digital marketing constructs and consumer perceptions into a holistic predictive model, as well as practical implications for businesspeople in designing marketing strategies based on content intensity and brand authenticity. The novelty of this research lies in the simultaneous testing of three variables in the context of the TikTok Shop, a relatively unexplored area in the digital marketing literature.